Adaptive Abstraction of 3D Scenes in Realtime - REDMOND, NIALL; DINGLIANA, JOHN (Eurographics Association, 2007)
We present an approach for creating abstracted renderings of 3D scenes in real-time. We create painterly renderings with edge detail using varying levels of abstraction dependent on regions of interest within a scene. Image space techniques are used to make the system real-time and as non-invasive as possible. This approach can also use object space information to segment the scene into visually important objects and unimportant data and background. Interactive frame rates are achieved by using graphics hardware to perform the computations.
Eurographics 2007 Short Papers
PUBLISHED
Keywords: Non-photorealistic rendering; Computer graphics; Three-dimensional graphics and realism; Colour, shading, shadowing and texture